2004
DOI: 10.1063/1.1724821
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared emission spectra of MgH and MgD

Abstract: High resolution Fourier transform infrared emission spectra of MgH and MgD have been recorded. The molecules were generated in an emission source that combines an electrical discharge with a high temperature furnace. Several vibration-rotation bands were observed for all six isotopomers in the X (2)Sigma(+) ground electronic state: v=1-->0 to 4-->3 for (24)MgH, v=1-->0 to 3-->2 for (25)MgH and (26)MgH, v=1-->0 to 5-->4 for (24)MgD, v=1-->0 to 4-->3 for (25)MgD and (26)MgD. The new data were combined with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 32 publications
3
57
0
Order By: Relevance
“…The vibrational bands v = 1 fi 0 to v = 3 fi 2 for MnH and v = 1 fi 0 to v = 4 fi 3 for MnD were observed. Analyses of the new spectra have provided improved ground state molecular constants for MnH and MnD.The same emission source that has proved to be very effective in providing spectra of other metal hydrides in our laboratory was used for MnH and MnD [12,13]. The infrared spectra of MnH/D were recorded between 800 and 1700 cm À1 at a resolution of 0.0085 cm À1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrational bands v = 1 fi 0 to v = 3 fi 2 for MnH and v = 1 fi 0 to v = 4 fi 3 for MnD were observed. Analyses of the new spectra have provided improved ground state molecular constants for MnH and MnD.The same emission source that has proved to be very effective in providing spectra of other metal hydrides in our laboratory was used for MnH and MnD [12,13]. The infrared spectra of MnH/D were recorded between 800 and 1700 cm À1 at a resolution of 0.0085 cm À1 .…”
mentioning
confidence: 99%
“…The same emission source that has proved to be very effective in providing spectra of other metal hydrides in our laboratory was used for MnH and MnD [12,13]. The infrared spectra of MnH/D were recorded between 800 and 1700 cm À1 at a resolution of 0.0085 cm À1 .…”
mentioning
confidence: 99%
“…The rotational, B (=5.7365078 cm −1 ), spin-rotational, γ (=2.63897 × 10 −2 cm −1 ), Fermi contact, b F (=1.0269 × 10 −3 cm −1 ), and dipolar, c (=1.598 × 10 −4 cm −1 ), parameters were held fixed at values determined from the analysis of the millimeter wave spectrum (Ziurys et al 1993). The centrifugal distortion correction to rotation, D (=3.543234 × 10 −4 cm −1 ), was held fixed at the value determined from the analysis of the tunable far-infrared spectrum (Zink et al 1990), whereas the centrifugal distortion correction to spin-rotation, γ D (=−5.77 × 10 −6 cm −1 ), was held fixed to the value obtained from the analysis of the Fourier transform infrared emission spectrum (Shayesteh et al 2004). A 4 × 4 matrix representation, constructed using a Hund's case (a βJ ), nonparity basis set, Ψ = |nΛ; SΣ; (JI)FΩM F >, was diagonalized to produce the eigenvalues and eigenvectors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no previous molecular beam optical spectroscopic studies of MgH. An extensive study of the field-free visible emission spectrum of MgH recorded at near Dopplerlimited resolution using Fourier transform spectroscopy has been reported by the Bernath group (Shayesteh & Bernath 2011;Shayesteh et al 2007Shayesteh et al , 2004Bernath et al 1985). A comprehensive review of the numerous spectroscopic studies performed on this molecule over the past century can be found in those publications.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory vibration-rotation spectra for a considerable number of metal hydrides are known with recent measurements of, for example, BeH (Shayesteh et al 2003a), MgH (Shayesteh et al 2004a), and CaH (Shayesteh et al 2004b); even the metal dihydrides BeH 2 (Shayesteh et al 2003b) and MgH 2 (Shayesteh et al 2003c) have been detected in the laboratory. Although metal hydrides such as MgH and CaH are detected in stellar atmospheres by their electronic transitions, there have been no infrared astronomical observations.…”
Section: Diatomic Moleculesmentioning
confidence: 99%